Asymmetric watermarking based on Contourlet transform and subspace projection - HE Mi; CHENG Li-zhi (Tongxin xuebao)
For the copyright protection of the digital image,a new asymmetric watermarking method of feature subspace projection based on Contourlet transform was presented.Embedding matrix（private key） and detecting matrix（public key） were constructed differently,where embedding matrix was kept secretly while detecting matrix was public.At the same time,the embedding matrix was independent on the host images.Robust subspace was obtained by Contourlet transformation.Using the embedding matrix,the arbitrary watermarking was embedded in the robust subspace.The de-tection function was constructed to detect whether an image had watermarking or not.The proposed method has good security,high detection probability and low false alarm probability.The stimulation shows that the proposed method is robust to many attacks.